“Could I have spoken in my own tongue”: : negotiating identity through second language performance in Villette - Lima, Ana Carolina Tavares Meira (Todas as Letras - Revista de Língua e Literatura, 2016)
This article examines how the character Lucy Snowe in Charlotte Brontë’s Villette perform a role similarly to actors on stage, when speaking in a foreign language, consequently reconstructing her social role and identity throughout the novel. Furthermore, I argue that some performances in second language oppose certain personal traits displayed by the character when speaking in her mother tongue. The findings of this research are based on an interdiscipli-nary approach, in which language theories are coupled with Victorian fiction studies, in order to analyse the discourse of the character, paying close atten-tion to how it shapes her identities.